Ne Bis In Idem in EU Competition Law – The Application of the Principle on the Relationship Between Article 102 TFEU and the Digital Markets Act - Holmberg,Emilia (2023)
During and after the adoption of the Digital Markets Act (DMA), concerns have been raised regarding the regulation’s relationship with the prohibition on abuse of dominant position in Article 102 TFEU. One possible concern regards the principle of ne bis in idem. The DMA is to be applied without prejudice to Article 102 TFEU. It is thus possible for an undertaking to be subject to obligations imposed by both Article 102 TFEU and the DMA. The aim of this thesis is therefore to examine how the principle of ne bis in idem is applied in EU competition law and how it will be applied on the relationship between Article 102 TFEU and the DMA. In order to fulfil this aim, a legal dogmatic method and an EU legal method are used. The case law from the CJEU regarding the application of the ne bis in idem principle in competition law cases has been criticised by Advocate Generals and legal scholars. In March 2022, the CJEU delivered two judgments that fundamentally altered the principle’s application in competition law. From the new case law, it follows that the objectives of Article 102 TFEU and the DMA will be of great importance when determining if there has been a viola-tion of the ne bis in idem principle. If Article 102 TFEU and the DMA pursue different objectives, a limitation of the ne bis in idem principle might be justi-fied in accordance with Article 52(1) of the Charter. However, if they pursue the same objective, a limitation can never be justified. The objective of Article 102 TFEU is to ensure that competition is not distort-ed in the internal market, whereas the objective of the DMA is to ensure a contestable and fair digital sector where gatekeepers are present. The objective of the DMA is thus complementary to, but different from, the objective of Article 102 TFEU. However, the objective of the DMA has been contested in the doctrine and it has been argued that the objective of the DMA includes the objective of Article 102 TFEU and competition law. It is therefore unclear whether the regulation pursues a different objective than Article 102 TFEU. The CJEU has been restrictive in finding the ne bis in idem principle applica-ble in competition law. It has also considered sector-specific regulation with the purpose of promoting competition to pursue a different objective than competition law. The court has, however, not provided further guidance on how to differentiate objectives. Given the restrictive approach of applying the ne bis in idem principle in com-petition law cases, this thesis concludes that parallel proceedings under the DMA and Article 102 TFEU will, in accordance with the current case law, likely constitute a justified limitation if the ne bis in idem criteria are found fulfilled. However, it falls within the jurisdiction of the CJEU to determine the objective of the DMA. Further litigation in the area is therefore needed and expected.
Keywords: EU law; Competition law; Article 102 TFEU; Digital Markets Act; DMA; Fundamental rights; Ne bis in idem